2013
DOI: 10.1002/cncr.28168
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of minorities and women in cancer clinical trials, a decade later: Have we improved?

Abstract: BACKGROUND: Inclusion of diverse groups of participants in cancer clinical trials is an important methodological and clinical issue. The quality of the science and generalizability of results depends on the inclusion of study participants who represent all populations among whom these treatment and prevention approaches will be used. METHODS: We conducted a systematic review using OVID as the primary source of reports included. Based on 304 peer-reviewed publications, diversity in the inclusion and reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 13 publications
8
147
0
1
Order By: Relevance
“…cancer, vascular surgery and cardiovascular trials 9, 10, 11, 12, 13), with the general media continuing to report that large gender gaps are still putting women at a disadvantage 14. This reporting has had serious effects on policy, with large amounts of money being allocated to study gender differences in healthcare 15.…”
Section: Introductionmentioning
confidence: 99%
“…cancer, vascular surgery and cardiovascular trials 9, 10, 11, 12, 13), with the general media continuing to report that large gender gaps are still putting women at a disadvantage 14. This reporting has had serious effects on policy, with large amounts of money being allocated to study gender differences in healthcare 15.…”
Section: Introductionmentioning
confidence: 99%
“…3 Consequently, care providers likely would be unaware and subsequently might not associate nonspecific symptoms such as joint discomfort or declines in kidney function with a cause other than rigors of therapy. Lack of awareness of the range and impact of sickling-related events also might be a consequence of underrepresentation of minorities in clinical trials, 22 which has resulted in limited evidence about differing responses to cancer therapy by race and ethnicity. 1 Alternatively, it must be emphasized that the scarcity of evidence about serious complications simply might reflect a not unusual rate of adverse events among SCT or SCD patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are minorities under-represented in clinical trials, but the overall racial and ethnic composition of clinical trials is not reported at an acceptable rate. Between 1990 and 2000, only 35.1% of treatment studies among cancer clinical trials reported race/ethnicity [2]. This number increased to 51.6% from 2001 thru 2010, but the percentage of blacks included in the analysis for the second decade decreased by 42% [2].…”
Section: Evidence Of Disparity Among Racial/ethnic Minoritiesmentioning
confidence: 99%